Back Cover: The Triplet Hydroxyl Radical Complex of Phosphorus Monoxide (Angew. Chem. Int. Ed. 49/2020). Issue 49 (24th November 2020) - Chu, Xianxu; Qian, Weiyu; Lu, Bo; Wang, Lina; Qin, Jie; Li, Jun; Rauhut, Guntram; Trabelsi, Tarek; Francisco, Joseph S.; Zeng, Xiaoqing
Abstract : The direct observation of a high‐energy radical pair consisting of a hydroxyl radical and phosphorus oxide is reported by J. S. Francisco, X. Zeng, and co‐workers in their Communication on page 21949 . The radical pair adopts triplet spin multiplicity and can thermally convert to metaphosphorous acid at extremely low temperatures.